Comparative study of dislocation density characterizations on silicon. Issue 1 (22nd September 2016) - Gallien, B.; Bailly, S.; Duffar, T.
Abstract : This study involves characterizing the sample with four different methods. Before each characterization, the sample is polished to obtain a mirror surface, by SiC grinding (EPA 1200 and 2400) and diamond paste polishing down to 1 μm. Then, specific chemical etching and dislocation density measurement are performed. Abstract : During production of silicon ingots for photovoltaic application, defects are created inside the crystal. Among these defects which impact photovoltaic efficiency, there are dislocations, linear defects mainly due to thermal stresses during ingot processing. Characterization of dislocations could take different ways. In this study, a comparison of 4 characterization methods for dislocation density in silicon is performed: one using manual counting, one using computer treatment of SEM pictures and two using optical dispersion evaluation. In order to show the strengths and weaknesses of each method, measurements are made on the same sample. Characteristic features of the sample, used for characterization, and all methods are first described. Then the procedure used for pairwise comparison of these methods is given. These coupled results are discussed in order to explain the differences observed in the dislocation density measured on the sample. Conclusions of this study give the application domain of each method. Remarks are formulated in order to help choosing a method consistent with the characterization purposes and the resources granted to it.